2008
DOI: 10.1007/s10661-008-0677-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hurricane Katrina on benthic macroinvertebrate communities along the northern Gulf of Mexico coast

Abstract: The effects of Hurricane Katrina on benthic fauna and habitat quality in coastal waters of Louisiana, Mississippi, and Alabama, USA, were assessed in October, 2005, 2 months after the hurricane made landfall between New Orleans, LA and Biloxi, MS. Benthic macrofaunal samples, sediment chemical concentrations, and water quality measurements from 60 sites in Lake Pontchartrain and Mississippi Sound were compared with pre-hurricane conditions from 2000-2004. Post-hurricane benthic communities had significant redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 20 publications
5
20
0
Order By: Relevance
“…The decrease in clam density during the hurricane years, 2005, 2008 and 2012 indicated distinct hurricane effects. These effects are supported by previous studies of benthic invertebrate impacts from Katrina and Rita (Poirrier et al 2008, Engle et al 2009) and Ike and Gustav (Ray 2009). We found that density changes in 6-20 mm clams accounted for most of the differences.…”
Section: Hurricane Effects and Recoverysupporting
confidence: 83%
“…The decrease in clam density during the hurricane years, 2005, 2008 and 2012 indicated distinct hurricane effects. These effects are supported by previous studies of benthic invertebrate impacts from Katrina and Rita (Poirrier et al 2008, Engle et al 2009) and Ike and Gustav (Ray 2009). We found that density changes in 6-20 mm clams accounted for most of the differences.…”
Section: Hurricane Effects and Recoverysupporting
confidence: 83%
“…We cannot resolve such acute effects with our limited data, but could the hurricanes have had longer-lasting effects on vibrio abundance? One significant effect of the storms was on the benthic communities, which showed declines in abundance and diversity as a result of scouring and changes in bottom water chemistry (20,57). We found that vibrio abundance was correlated with turbidity, and an increase in the turbidity of the lake appears to be correlated with the loss of the community services of benthic filter feeders, such as the clam Rangia cuneata (57).…”
Section: Discussionmentioning
confidence: 70%
“…A study of estuaries in the northern Gulf of Mexico by Rakocinski et al (1997) determined that the effect of natural gradients in depth, salinity, and sediment composition made evaluating the effect of sediment pollution in benthic macrofauna communities. During storm events in the Gulf of Mexico, scouring of the sediment and salinity changes have been identified as the primary factors contributing to changes in the diversity and abundance of benthic macrofauna communities difficult (Mallin et al, 1999;Engle et al, 2009). Seasonal hypoxic zones accompanied by sulfate reduction and sulfide formation were also found to reduce benthic macrofauna abundance, diversity, richness, and evenness (Rabalais et al, 2001;Montagna & Ritter, 2006).…”
Section: Benthic Macrofaunamentioning
confidence: 99%